Comparative Study of the Perioperative Care of Head and Neck Surgical Patients with and without Central Venous Pressure Line - Ali, Amjad; Khurram, Muhammad; Khan, Fozia Anis; Shah, Syed Muhammad Khalid (Journal of Rawalpindi Medical College, 2026)
Background: To study the practice of central venous pressure (CVP) line insertion in perioperative head and neck surgical patients. Methods: In this comparative study, patients undergoing elective major head and neck surgery were divided into two groups. Group I (n=22) included those with CVP line insertion and Group II (n=38) without CVP line insertion.Perioperative patient care was assessed in terms of clinical (perioperative hypotension, oliguria, and transfusion requirement) and laboratory parameters (pre and post operative hemoglobin, and estimated blood loss). Results: No significant difference was noted between the two groups in terms of age, gender, weight, and pre-operative hemoglobin levels. Both groups differed significantly in terms of co morbidities (68%:36%, p<0.05), hypotension (50%:15%, p<0.05), oliguria (31.8%:7.8%, p<0.05), post operative haemoglobin (9.75±1.10:10.52±1.11g, p<0.05), and estimated blood loss (846 ±420:588±290 ml, p<0.05). Conclusion: CVP line insertion in major head and neck surgery patients is influenced by presence of co-morbidities. Perioperative patient care does not improve with CVP line insertion. Key Words: Central Venous Pressure, Head and Neck, Surgery, Co-morbidity